HODGE, B. & CORONADO, G. (2012). Mexico and its others: A chaos theory approach - Williamson, Rodney (Revista Latinoamericana de Estudios del Discurso, 2020)
HODGE, B. & CORONADO, G. (2012). Mexico and its others: A chaos theory approach. Ottawa: LEGAS, 248 pp. ISBN: 978-1-897493-31-1